Multinationality and Performance among British Manufacturing Companies - Grant, Robert M. (Journal of International Business Studies, 1987)
Over the period 1972–84, profitability among 304 large, British manufacturing companies was positively related to their degree of multinationality. Moreover, increases in overseas production were strongly associated with increases in sales and profitability. The profitability of multinational growth over the whole period was independent of its destination, supporting the view that the primary source of the superior performance of multinationals was competitive advantage rather than the higher rate of profit in the industries of other countries.